The use of methods of psychiatric education in the prevention of mental pathology by a psychiatrist outpatient consultation - Shapovalova LA; Shapovalov KA (Annals of Psychiatry and Treatment - Peertechz Publications, 2021)
Introduction: Educating the population in the field of mental health includes a set of educational, upbringing, agitation and propaganda activities aimed at promoting a healthy lifestyle, preventing diseases, maintaining and strengthening health, increasing the ability of people to work, and prolonging their active life. Aim: Determine the role and place of psychoprophylaxis of psychiatric education and in the structure of the work of a psychiatrist of an outpatient consultation appointment. Material and methods: The analysis of 5 qualification works of a psychiatrist for the use of methods of psychiatric education of the contingent of patients of outpatient consultation was carried out. The depth of the study was 24 years. When working on the material, the following methodological approaches were used: systemic, complex, dynamic, normative, quantitative and situational. Analysis methods included: historical, analytical and comparison. The following techniques were used for the analysis: groupings, absolute values, continuous and selective observations. Results: Psychiatric reception in the advisory department of GAUZ RK "CDC" is carried out by one specialist. Individual psychoeducation, psychiatric education and psychoprophylaxis accompany the entire treatment process of persons with mental disorders. The psychiatrist of the regional center is constantly engaged in psychoeducation of the population, works with the medical staff of the institution and central regional hospitals, and is engaged in methodological and research work. Discussion: Health education in psychiatry in all forms contributes to a wider medical prevention of the development of pathology in the mental sphere, as well as to the improvement of already developing diseases and the prevention of relapse of cured diseases. Despite the fact that the psychiatrist simultaneously deals with such topics that are not of a pronounced psychological nature, they always include professional problems, since they relate to human relationships, provide people with information, recommendations, advice and act on them emotively. Conclusions: Sanitary educational work in psychiatry is aimed at increasing the level of knowledge of the population about mental disorders, mastering methods of protection from stress, the harmful effects of bad habits. Individual psychiatric education accompanies the entire treatment process. A psychiatrist should work with every patient who has signs of mental pathology and through the dissemination of medical and hygienic knowledge, education of sanitary and hygienic skills in order to preserve and strengthen health, improve sanitary and hygienic culture, taking into account gender, age, climatic and geographical features, national customs, traditions and other factors can affect his individual health. During an outpatient appointment, all psychiatrists, without exception, need to conduct individual conversations on the prevention of mental illness, during which it is important to explain to patients what pathology the patient has, what kind of treatment is required, what preventive measures for mental disorders exist (psychoprophylaxis, psychohygiene). Involvement of the patient in individual prevention and participation in the treatment of already developed pathology in psychiatry should be carried out using various forms of health education. It should be constructive and focused on promoting ways of recovery. Psychoeducation, psychiatric education and psychoprophylaxis, conducted by a psychiatrist, teach patients to provide themselves with possible and affordable types of preventive actions, increases the effectiveness of using the available material resources and improves the quality of life. They are types of psychological intervention aimed at achieving positive changes in the cognitive, emotional and behavioral spheres of the sick person.